Effect of Endocuff-assisted colonoscopy on adenoma detection rate: meta-analysis of randomized controlled trials - Williet, Nicolas; Tournier, Quentin; Vernet, Chloé; Dumas, Olivier; Rinaldi, Leslie; Roblin, Xavier; Phelip, Jean-Marc; Pioche, Mathieu (Endoscopy, 2018)
Background Yield of Endocuff-assisted colonoscopy (EAC) compared with standard colonoscopy is conflicting in terms of adenoma detection rate (ADR). A meta-analysis of randomized controlled trials (RCTs) appears necessary. Methods PubMed and Google Scholar were searched in December 2017. Abstracts from Digestive Disease Week and United European Gastroenterology Week meetings were also searched to 2017. All RCTs comparing EAC with standard colonoscopy were included. Analysis was conducted by using the Mantel–Haenszel models. Heterogeneity was quantified using the I2 test.Results Of the 265 articles reviewed, 12 RCTs were included, with a total of 8376 patients (EAC group 4225; standard colonoscopy group 4151). In the meta-analysis, ADR was significantly increased in the EAC group vs. the standard colonoscopy group (41.3 % vs. 34.2 %; risk ratio [RR] = 1.20, 95 % confidence interval [CI] 1.06 to 1.36; P = 0.003; I2 = 79 %), especially for operators with low-to-moderate ADRs (< 35 %): RR = 1.51, 95 %CI 1.35 to 1.69; P < 0.001; I2 = 43 %). In contrast, this benefit was not reached for operators with high ADRs (> 45 %): RR = 1.01, 95 %CI 0.93 to 1.09; P = 0.87; I2 = 0.0 %). The mean number of adenomas per patient tended to be higher with EAC (mean difference = 0.11 adenomas/patient, 95 %CI – 0.17 to 0.38). Similar results were shown for polyp detection rates (61.6 % vs. 51.4 %; RR = 1.20, 95 %CI 1.06 to 1.36; P = 0.004). Use of the Endocuff did not impact the cecal intubation rate (95.1 % vs. 95.7 %; P = 0.08), or the procedure time compared with standard colonoscopy. Adverse events related to Endocuff were rare and exclusively mild mucosal erosion (4.0 %; 95 %CI 2.0 % to 8.0 %). Conclusion With moderate-quality evidence, this study showed an improvement in ADR with EAC without major adverse events, especially for operators with low-to-moderate ADRs.